Wind Power : Technology Brief (International Renewable Energy Agency IRENA, 2016)
The size of wind turbines has continuously increased over several decades to boost power generation from this key renewable energy source. As this technology brief from IRENA and IEA-ETSAP notes, large-scale wind farms and larger turbines drive the ongoing reduction of electricity costs.